Numerical Analysis of the Failure of a 3D-Printed Knee Joint for a Transfemoral Amputee - Majid Amelia Arsyl; Achmad Syaifudin (Journal of Medicine and Health Technology, 2025)
A leg prosthesis is a tool that can help people with disabilities due to amputation or birth defects. Prosthetic leg products created through the 3D printing process on the knee joint have been reported to have cracked after two months of use. The purpose of this study was to observe the causes of failure of knee joints in prosthetic legs printed using the 3D printing method. The numerical method based on the finite element method, ANSYS Workbench 2023, was chosen to complete the structural simulation. The model parameters observed in the simulation were the printing orientation, model position, and equivalent plastic strain of PETG, ABS, and PLA. Several print-direction positions were considered in this simulation, namely 0°, 45°, and 90°. Static simulation of the structure was performed because only the static forces acted on the knee joint. Static forces were obtained by applying the principle of static equilibrium to rigid objects. The results of the numerical simulation showed that damage to the knee joint made of PTEG was caused by the plane of 90°. The orientation position causes the force received in the perpendicular direction of the knee joint component; thus, it tends to break the printing layers. The ideal printing orientation for the knee joint is 0° orientation. This orientation is considered suitable because it has the highest safety factor compared to other orientations.